2010
DOI: 10.18632/oncotarget.140
|View full text |Cite
|
Sign up to set email alerts
|

The secretory small GTPase Rab27B as a marker for breast cancer progression

Abstract: AbstrAct:In contemporary oncology practice, an urgent need remains to refine the prognostic assessment of breast cancer. It is still difficult to identify patients with early breast cancer who are likely to benefit from adjuvant chemotherapy. Although invasion of cancer cells is the main prognostic denominator in tumor malignancy, our molecular understanding and diagnosis are often inadequate to cope with this activity. Therefore, deciphering molecular pathways of how tumors invade and metastasize may help in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Equivalent amounts of total protein, as determined by BCA assay (Pierce Biotechnology, Rockford, IL, USA), from HEK cells or control and patient melanocyte extracts, were loaded onto 4–12% Tris‐Glycine gels. After blotting, the nitrocellulose membranes (Invitrogen) were probed with a rabbit polyclonal antibody specific for RAB27B (Barral et al., 2002), a mouse monoclonal antibody specific for RAB27A [BD Biosciences, San Jose, CA, USA; (Hendrix et al., 2010a)], a mouse monoclonal α‐tubulin antibody (loading control, Sigma), a GFP mouse monoclonal antibody (Millipore), a mouse monoclonal MYO5A antibody (Sigma), and a rabbit polyclonal MLPH antibody (Proteintech Group Inc.), followed by incubation with HRP‐labeled secondary anti‐mouse or anti‐rabbit antibodies (Amersham Biosciences, Piscataway, NJ, USA). The antigen–antibody complexes were detected with an Enhanced Chemiluminescence (ECL) kit (Amersham Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…Equivalent amounts of total protein, as determined by BCA assay (Pierce Biotechnology, Rockford, IL, USA), from HEK cells or control and patient melanocyte extracts, were loaded onto 4–12% Tris‐Glycine gels. After blotting, the nitrocellulose membranes (Invitrogen) were probed with a rabbit polyclonal antibody specific for RAB27B (Barral et al., 2002), a mouse monoclonal antibody specific for RAB27A [BD Biosciences, San Jose, CA, USA; (Hendrix et al., 2010a)], a mouse monoclonal α‐tubulin antibody (loading control, Sigma), a GFP mouse monoclonal antibody (Millipore), a mouse monoclonal MYO5A antibody (Sigma), and a rabbit polyclonal MLPH antibody (Proteintech Group Inc.), followed by incubation with HRP‐labeled secondary anti‐mouse or anti‐rabbit antibodies (Amersham Biosciences, Piscataway, NJ, USA). The antigen–antibody complexes were detected with an Enhanced Chemiluminescence (ECL) kit (Amersham Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…Because exosome secretion is closely related to cancer and tumor progression (124), increased Rab27dependent exosome secretion may cause cancer or tumors. It is particularly noteworthy that alteration of Rab27 expression has often been observed in cancer cells (125)(126)(127)(128) and that overexpression and knockdown of Rab27 in cancer cells have been found to affect their invasiveness (129)(130)(131)(132).…”
Section: Role Of Rab27 Effectors In the Secretory Pathways Of Secretomentioning
confidence: 99%
“…reprogramming from oxidative phosphorylation towards aerobic glycolysis in breast cancer cells [11]. Clinical studies indicated that the elevated expression of Rab27b was correlated with lymph node metastasis and the secretory Rab27b was an independent risk factor for survival of breast cancer patients [12]. [14].…”
Section: Overexpression Of Rab27b Enhanced the Invasive Capacities Anmentioning
confidence: 99%